Swiss trade during the COVID-19 pandemic: An early appraisal - Konstantin Büchel; Stefan Legge; Vincent Pochon; Philipp Wegmüller (Swiss Journal of Economics and Statistics, 2020)
This study uses trade data from Switzerland's Federal Customs Administration to examine the impact of Covid-19 on international goods trade between January and July 2020. We show that Swiss trade during that period fell by 11% compared to 2019 and that the contraction following the "Federal Lockdown" in mid-March was considerably steeper than the Swiss trade collapse in the aftermath of the Lehman Brothers bankruptcy in September 2008. Examining cross-country variation in Covid-19 cases, the stringency of containment measures, and Swiss trade flows, we document that the pandemic adversely affected both the demand and supply side of foreign trade, while trade restrictions and exchange rate fluctuations played no major role behind the rapid decline of Swiss trade in the first half of 2020.
Keywords: E32; F14; H12; I18; 330; Covid-19; Trade; Switzerland